Assessing the Need for Information on Traumatic Injuries of Parents Raising Children - Aleksandravičiūtė, Eglė; Gedrimė, Lina (Slauga. Mokslas ir praktika, 2020)
Traumatic injuries to children are a pressing health issue in society. The main processes that help reduce the risk of child injuries are parental care for children, primarily by determining the average differences in child injuries. The need for information for parents is related to child and adolescent trauma based on the understanding that collaboration between nurses and parents can improve the quality of health in children and adolescents. Parents have different perceptions of the consequences of injuries and the consequences of prevention initiative. Parents' knowledge of traumatic injuries reduces children's exposure to the consequences of traumatic injuries suffered by children. Cooperation between health care professionals ensures the quality of parental knowledge. This article analyzes the need for information of parents (necessity, necessity), the level of knowledge. Introducing the results of the study.
Keywords: parental knowledge needs; children's trauma; awareness; traumatic injuries